Status of some populations of Mexican salamanders (Amphibia: Plethodontidae) - Parra-Olea, Gabriela (1999)
Populations of Mexican plethodontid salamanders have been surveyed non-systematically over the last 25 years. In light of many reports of disappearance of amphibians around the world, we checked for persistence of reported species at ten of these sites. All of the commoner species persist (we observed individuals representing a total of 30 species). While observed densities of many species of Mexican plethodontids are lower to much lower than was the case 20 to 25 years ago, evidence for recent extinctions, such as has been reported for amphibian taxa elsewhere, is equivocal or lacking. Habitat modification has contributed to difficulties in finding certain species.